The Natural Course of Compensatory Lumbar Curves in Nonoperated Patients With Thoracic Adolescent Idiopathic Scoliosis. Issue 2 (15th January 2019) - Ohashi, Masayuki; Watanabe, Kei; Hirano, Toru; Hasegawa, Kazuhiro; Katsumi, Keiichi; Shoji, Hirokazu; Mizouchi, Tatsuki; Takahashi, Ikuko; Endo, Naoto
Abstract : Study Design: A retrospective, long-term follow-up study. Objective: We investigated the natural course of compensatory lumbar curves in patients with primary thoracic adolescent idiopathic scoliosis (AIS). Summary of Background Data: The natural course of compensatory lumbar curves in primary thoracic AIS remains unknown. Methods: Inclusion criteria were right-sided primary thoracic AIS ≥30° with a Lenke lumbar modifier of A or B at skeletal maturity and ≥30 years of age at the time of the survey. Fifty-one patients (mean age, 40.2 yr) returned for a follow-up evaluation (follow-up rate, 34.2%). Patients were classified into three groups based on the lumbar modifier (A or B) and direction of L4 tilt [right (R) or left (L)] (AR, n.11; AL, n.18; and B, n.22). At the time of the survey, 42 patients underwent radiological examinations and 37 underwent lumbar magnetic resonance imaging. Quality of life questionnaires were completed in all patients and in a 1:1 matched control group (no history of scoliosis). Results: The thoracic curves had significantly progressed in all patient groups, while the compensatory lumbar curve progressed only in the B group. The C7 translation and L4 tilt shifted to the right in the AR and AL groups, but did not change in the B group. As a result, the L4 tilt (median, 11°) and C7 translation (18.6 mm) tended to be the greatest in the AR group. The incidences of Modic changes at L4/5 discs and ≥3 cm on the visual analogue scale for low back pain were significantly higher in the AR group (77.8% and 54.5%, respectively) compared with that in the other groups. Conclusion: The natural course of compensatory lumbar curves is dependent on the lumbar modifier and direction of L4 tilt. Adolescent patients with right-sided primary thoracic AIS (≥30°) with L4 tilted to the right should be considered for periodic follow-ups into adulthood. Level of Evidence : 4 Abstract : We investigated the natural course of right-sided primary thoracic adolescent idiopathic scoliosis, focusing on compensatory lumbar curves. The incidence of Modic changes and low back pain at middle age were the highest in Lenke lumbar modifier A curves with rightward L4 tilt.